2018
DOI: 10.5863/1551-6776-23.5.379
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pulmonary Outcomes, Microbiology, and Serum Antibiotic Concentrations in Cystic Fibrosis Patients

Abstract: OBJECTIVES To determine the frequency of subtherapeutic exposure to intravenously administered β-lactam antibiotics in a cohort of cystic fibrosis (CF) patients who were treated for a pulmonary exacerbation, and its impact on pulmonary function. METHODS Nineteen CF patients between the ages of 5 and 21 years treated at Children's National Health System for a pulmonary exacerbation were followed between March 2015 and August 2016 in a prospective, longitudinal study. Pharmacokinetic modeling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…While no statistical differences were noted, trends were present that showed patients receiving therapeutic antibiotics had a higher relative improvement of FEV 1 , and FEV 1 /FVC at post-recovery compared to onset of the exacerbation than those in the subtherapeutic group (FEV 1 28.8 vs 14.8, p = 0.11; FEV 1 / FVC 9 vs 1.1, p = 0.07). This corroborates our findings previously published on this same cohort of patients where significant differences were found in non-normalized pulmonary function between the two groups, with higher recovery in those achieving therapeutic beta-lactam drug exposure 31 .…”
Section: Changes In Alpha Diversity and Community Composition Followisupporting
confidence: 92%
See 2 more Smart Citations
“…While no statistical differences were noted, trends were present that showed patients receiving therapeutic antibiotics had a higher relative improvement of FEV 1 , and FEV 1 /FVC at post-recovery compared to onset of the exacerbation than those in the subtherapeutic group (FEV 1 28.8 vs 14.8, p = 0.11; FEV 1 / FVC 9 vs 1.1, p = 0.07). This corroborates our findings previously published on this same cohort of patients where significant differences were found in non-normalized pulmonary function between the two groups, with higher recovery in those achieving therapeutic beta-lactam drug exposure 31 .…”
Section: Changes In Alpha Diversity and Community Composition Followisupporting
confidence: 92%
“…Another study found a strong correlation between poor lung function and low species richness 8 , while two others showed that lower alpha diversity, measured by Shannon diversity index, was associated with worsening pulmonary function 28,30 . Our previously published analysis of this patient cohort comparing antibiotic PK and lung function found subtherapeutic beta-lactam antibiotic exposure was associated with less improvement of lung function 31 . In this study, we also saw similar trends using normalized lung function data.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A sparse PK sampling design was used similar to the one we had previously published. 11 Briefly, samples were collected after achieving steady state (>24 hours after initiation of antibiotics) and were obtained at four time points: trough (×2), peak (1 hour after infusion), and mid-dose (3-4 hours after infusion). Samples were placed on ice and processed immediately to maintain concentration integrity, and then were frozen at −80°C.…”
Section: Pk Sampling Design and Plasma Concentration Determinationmentioning
confidence: 99%
“…There the free drug plasma concentrations for ceftriaxone, ceftazidime, piperacillin, and meropenem were determined from each sample using multiplex liquid chromatography-mass spectroscopy. 11 PK/PD modeling PK modeling of beta-lactam antibiotics was performed using Bayesian estimation in MW/Pharm V.3.80 (Mediware), as previously published. 8 9 11 Briefly, study subject age, weight, height, serum creatinine (measured at hospital admission), antibiotic dose, and measured plasma concentrations were all incorporated into the model to develop the time-concentration curve.…”
Section: Pk Sampling Design and Plasma Concentration Determinationmentioning
confidence: 99%